Роль інформаційного маркетингу в сфері соціальних послуг - Демчук, Юліана; Кравець, Руслан (Видавництво Львівської політехніки, 2018)
There are many different social services in the world. Marketing is very important for their functioning. Effectiveness of marketing concepts. Marketing activity is relevant today.
Keywords: маркетинг; соціальні послуги; маркетолог; концепція; маркетинговий комплекс; призначення